The Probing: Berkedaulatan Rakyat dengan Hikmat - Purwo Santoso (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2020)
As a teaching, democracy is very ambitious: to rule (the ruled becomes) the government. Ordinary people, who are culturally comfortable in the position of slave labor, must change their position / character / role: determining the choice of those who control them. In the awareness that the people manage their sovereignty in their own way and the processes for actualizing their sovereignty (discursive design), the way of being democratic / sovereign is to oversee the enactment of the policy to be wise (meta-policy).